Integrated Personality Profiling Framework Using Traits And Factors Theory For Malaysian HLI Enrolment : A New Approach - Md Saad, Mohd Shamsuri; Yunus, Ahmad Rozelan; Syed Hassan, Syed Najmuddin; Kamarudin, Mohd Fauzi; Abd Majid, I. (Penerbit Universiti,UTeM, 2018)
Personality profiling is important especially in education and human resource management.Inability to identify individuals’personality may cause misunderstanding of ones potential;and further more, he/she might fail to recognize his/her own career or academic direction.This study aimed to develop an integrated personality framework;using Trait and Factor Theory of Occupational Choice.The completed framework was used as the core concept of integrated profiling instrument,named as Integrated Personality Profiling (i-PRO).The main beneficiary of the completed (i-PRO) will be students, academics and non-academic personnel.The sample for this initial study was 380 students from one Higher Learning Institution (HLI) in Malaysia.The sampling method used was random sampling.The study was done to explore the Holland’s 3-code interest traits among engineering students of the said HLI.One of the developed domain used in this initial study was career interest domain.The Holland’s 3-code typologies for Higher Learning Institution (HLI) respondents are Investigative, Social and Realistic (I, S, R).